EFISIENSI SOSIAL DAN FINANSIAL BANK SYARIAH DI INDONESIA: PENDEKATAN NONPARAMETRIK - Rusydiana, Aam Slamet (Riset Akuntansi dan Keuangan Indonesia, 2019)
Every single effort or process taken by Islamic bank to maximize output should also uphold Islamic values, so that maqashid sharia (maslahah-sharia objectives) would be authomatically achieved. There were some research conducted to measure Islamic bank performance using maqashid sharia framework. However, these studies were not explicitly addressing the issue of cost-saving strategies within the framework of efficiency measurement. It is therefore this paper aims to have financial and social efficiency in one assessment framework that is social-financial efficiency quadrant (SFEQ). Hence, in order to measure efficiency level of Islamic Banking Industry this study use Data Envelopment Analysis (DEA) method and employ Banxia Frontier Analyst 3.1 for data analysis. Within the SFEQ framework, the study revealed that Sharia Panin Bank and Sharia Bukopin Bank are excellent since both are within the first quadrant.Whereas Sharia Maybank, and BCA Sharia are considered good at the second quadrant; Bank Sharia Mandiri (BSM), Bank Muamalat, Bank Rakyat Indonesia Sharia (BRIS), Bank Negara Indonesia Sharia (BNI) and Mega Sharia are fair at the third; and Victoria Sharia, and Bank Jabar Banten Sharia (BJB) are poor at the fourth sequentially. It is urge for Islamic bank that are in low level of ‘social efficiency’ to have a critical policy to keep in line with the five factor of maqashid sharia apart of having efficiency in order to reach maslahah.